Importance of Using Film in Social Studies Education (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
The COVID-19 pandemic forced educators to rework their entire delivery method for instruction to students. It has allowed technology and media, such as film, to take a forefront. Film is a key component to the successful delivery of social studies content to students. Utilizing film to deliver content in social studies provides many different benefits for students. This article explores several ideas including the importance of utilizing film to teach content within social studies, the types of film to use, different concepts to be taught using film as well as the cautions of using film.
Keywords: social studies; film; history; media